PROBLEMS OF VALEOLOGICAL CULTURE OF STUDENTS. - G.N. Ernazarov, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article presents the results of a stating pedagogical experiment to identify the need for a healthy lifestyle of student youth, their relationship and knowledge, compliance with the rules and their practical application.